Liminar em mandado de segurança - Lara, Jefferson (2019)
The writ of mandamus is a constitutional action aimed at protecting the individual against abuses perpetrated by authorities. One of the ways the legislator found to achieve this constitutional protection was the provision of preliminary injunction, given urgently, after a brief cognition (before the contradictory offer). The Law no 12.016/2009 regulates the writ of mandamus, establishing requirements, procedures and prohibitions for the granting of preliminary injunctions and for the development of the mandate process as a whole. The current paper intends to highlight some relevant points about preliminary injunctions, in particular their legal nature, the requirements for granting them, the appeal against their rejection, the prohibition hypotheses provided by law and the effects of the revocation of the measure